A new species of Tiodus (Hemiptera, Cercopidae) with a key to species of the genus - Paladini, Andressa; Cavichioli, Rodney Ramiro (Zootaxa, 2017)
Tiodus sakakibarai sp. nov. from Peru (Puno) is described and illustrated. This new spittlebug species is characterized by the following features: postclypeus orange, moderately inflated, slightly angulated in profile; tegmina black with two transcommissural reddish-orange transverse bands; aedeagus robust not bifid. An identification key to species of the genus is provided.